2013
DOI: 10.1007/s11192-013-1113-6
|View full text |Cite
|
Sign up to set email alerts
|

Growth in the number of references in engineering journal papers during the 1972–2013 period

Abstract: The number of references per paper, perhaps the best single index of a journal's scholarliness, has been studied in different disciplines and periods. In this paper we present a four decade study of eight engineering journals. A data set of over 70000 references was generated after automatic data gathering and manual inspection for errors. Results show a significant increase in the number of references per paper, the average rises from 8 in 1972 to 25 in 2013. This growth presents an acceleration around the ye… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 10 publications
5
21
0
Order By: Relevance
“…However; in terms of the increasing average numbers of references per page over the two periods, the three publication types generally present the same trend which is in line with the observations of other studies of journal literature (e.g., Krampen, ; Marx & Bornmann, ; Peritz & Bar‐Ilan, ; Ucar et al, ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However; in terms of the increasing average numbers of references per page over the two periods, the three publication types generally present the same trend which is in line with the observations of other studies of journal literature (e.g., Krampen, ; Marx & Bornmann, ; Peritz & Bar‐Ilan, ; Ucar et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…Studies focusing on journal literature show that the absolute numbers of references per paper differ among disciplines and periods, but there is a general increase in the average number of references in all fields. Ucar et al () presented a significant increase in the number of references per paper in engineering journals, the average rises from 8 in 1972 to 25 in 2013. Peritz and Bar‐Ilan () reported that the mean number of references for articles in the journal Scientometrics increased from 15.1 in 1990 to 19.8 in 2000.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strongest increase is visible for the natural sciences, engineering, and medicine. Similar results based on papers published in engineering journals were published by Ucar et al (2014). The consequences for an indicator based on cited references are that it is calculated separately for the papers published in different publication years (this is the standard procedure in field-normalization).…”
Section: Referencing Patterns In the Datamentioning
confidence: 67%
“…The number of references per article is also an important indicator in this context, because it reflects the social links in science, the stage of discipline development and the conditions of access to information by the scientific community [12,21,22]. The results show a significant increase in the average number of references, rising from 33.9 in 2000 to 55.7 in 2012.…”
Section: Nationality and Internationality Of Referencesmentioning
confidence: 99%